The Economic and Monetary Union: Current and Future Prospects - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 1999)
The euro was adopted as legal tender, albeit in a virtual form, by eleven countries of the European Union on January 1, 1999, with the intention that notes and coins denominated in euros would be introduced and the national currencies would be phased out during the first six months of that year and that the euro would be fully operational by 2002. This paper first reviews the current position of the EMU member states in relation to the convergence criteria under the Maastricht Treaty and finds that there must have been a considerable degree of "fudge" for the criteria to have been met. The paper next looks at the central role of aggregate demand in the EMU and at concerns about unemployment. It then examines the prospects of the current EMU arrangements, concluding that they are highly deflationary. To overcome the deflationary bias of current proposals and as a means to alleviate the serious unemployment problem, the authors recommend that the European Central Bank be enhanced by (1) the development of a new institution, the European Union Development Bank, and (2) a modification of the Stability and Growth Pact.
Keywords: 330